Nano-, Bio-, Info-Tech Sensors and Wearable Systems (SPIE / International Society for Optical Engineering, 2021)
Proceedings of SPIE offer access to the latest innovations in research and technology and are among the most cited references in patent literature. The papers in this volume were part of the technical conference on Nano-, Bio-, Info-Tech Sensors and Wearable Systems held on 22-26 March 2021 Online Only, United States.